1978
DOI: 10.1037/0022-0167.25.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Impressions of counselors as a function of counselor physical attractiveness.

Abstract: This analogue research assessed the effects of counselor physical attractiveness and interactions between attractiveness and counselor and subject sex. Forty male and 40 female undergraduates rated their first impressions of a counselor and their expectations for counseling outcome on the basis of a photograph of either an attractive or an unattractive person and a brief, audiotaped self-introduction by either a male or a female counseling psychologist. Attractiveness did not show main effects but did interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
2

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 12 publications
3
55
2
Order By: Relevance
“…The results indicated that the students rated the physically attractive counselor as more intelligent, friendly, assertive, trustworthy, competent, warm, likeable, and helpful. Two other studies (Carter, 1978;Lewis & Walsh, 1978) offer slightly different findings. Both suggest that the effect of counselor physical attractiveness on perceived attractiveness may be differentially related to the sex of the counselor and the client.…”
Section: Characteristics Associated With the Counselormentioning
confidence: 87%
“…The results indicated that the students rated the physically attractive counselor as more intelligent, friendly, assertive, trustworthy, competent, warm, likeable, and helpful. Two other studies (Carter, 1978;Lewis & Walsh, 1978) offer slightly different findings. Both suggest that the effect of counselor physical attractiveness on perceived attractiveness may be differentially related to the sex of the counselor and the client.…”
Section: Characteristics Associated With the Counselormentioning
confidence: 87%
“…The female and male actors who portrayed supervisors were between 40 and 45 years of age and were judged by a panel to be similar in physical attractiveness and in their portrayal of a supervisor. Several studies have demonstrated physical attractiveness to be a strong and pervasive determinant of initial impression formation and as a variable affecting counseling relationships (Carter, 1978;Cash, Begley, McGown, & Weiss, 1975;Cash & Salzbach, 1978;Lewis & Walsh, 1978). In view of this evidence, actors of similar attractiveness were used to avoid possible contamination.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the counselor's qualities of unconditional positive regard and a nonpossessive attitude toward the client also enhance the perception of the counselor as an attractive individual. As is the case with perceived expertness and trustworthiness, there are several studies that support the concept of counselor social attractiveness (Carter, 1978;Cash, Begley, McCown, & Weise, 1975;Cheney, 1975;Kerr & Dell, 1976;Lacrosse, 1975;Lewis &Walsh, 1978;Schmidt & Strong, 1971;Sell, 1974;Vargas & Borkowski, 1982).…”
mentioning
confidence: 99%